Psychological precursors of entrepreneurial intentions among higher education students in Ghana - Inuusah Mahama; Peter Eshun; Patricia Mawusi Amos; Theresa Antwi; Bernard Mensah Amoako; Veronica Esinam Eggley (Springer, 2023)
Abstract Background Entrepreneurship is seen as the solution to graduate unemployment in Ghana, and students are required to take a course on entrepreneurship that teaches them how to work for themselves. Therefore, this study investigated the psychological precursors of entrepreneurial intentions among higher education students. Methods Using the analytical cross-sectional survey design, 250 participants were sampled from public universities to participate in the survey. Participants were required to respond to three constructs (entrepreneurial scaffolding, psychological capital, and entrepreneurial intentions). The data analyses were performed using multivariate regression. Results The study's findings showed that entrepreneurial scaffolding and psychological capital were significant predictors of entrepreneurial intentions. Conclusion The researchers concluded that students' convictions about succeeding or failing and plans to engage in entrepreneurial behaviours depended on proper entrepreneurial guidance and a positive mindset. As a result, higher education institutions and career counsellors in Ghana should be strengthened and include practical guides to entrepreneurial training, thereby reducing graduate unemployment in Ghana.